2017
DOI: 10.1186/s12891-017-1897-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of multiple versus single hyaluronic acid injections: a systematic review and meta-analysis

Abstract: BackgroundIntra-articular hyaluronic acid (IA-HA) is a common therapy used to treat knee pain and suppress knee inflammation in knee osteoarthritis (OA), typically prescribed in regimens ranging from a single injection to 5 weekly injections given once weekly. We conducted a systematic review to determine the efficacy of IA-HA, with subgroup analyses to explore the differences in knee pain and adverse events (AEs) across different dosing regimens.MethodsWe conducted a systematic search of the literature to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 51 publications
1
52
1
7
Order By: Relevance
“…However, when lifestyle modification, physical therapy, and nonsteroidal anti‐inflammatory drugs lack to allay OA symptoms, intra‐articular (i.a.) hyaluronic acid (HA) injections are frequently used . Various physiological effects contribute to the mechanisms by which viscosupplementation with HA exerts its clinical and chondroprotective effect: increases the proteoglycan synthesis, reduces the production and activity of soluble pro‐inflammatory mediators and degradative enzymes (e.g., matrix metalloproteinases, MMP) and alters the behavior of immune cells .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when lifestyle modification, physical therapy, and nonsteroidal anti‐inflammatory drugs lack to allay OA symptoms, intra‐articular (i.a.) hyaluronic acid (HA) injections are frequently used . Various physiological effects contribute to the mechanisms by which viscosupplementation with HA exerts its clinical and chondroprotective effect: increases the proteoglycan synthesis, reduces the production and activity of soluble pro‐inflammatory mediators and degradative enzymes (e.g., matrix metalloproteinases, MMP) and alters the behavior of immune cells .…”
mentioning
confidence: 99%
“…hyaluronic acid (HA) injections are frequently used. [6][7][8][9] Various physiological effects contribute to the mechanisms by which viscosupplementation with HA exerts its clinical and chondroprotective effect: increases the proteoglycan synthesis, reduces the production and activity of soluble proinflammatory mediators and degradative enzymes (e.g., matrix metalloproteinases, MMP) and alters the behavior of immune cells. 10 HA has also shown an antioxidant effect in various systems, thus providing protection to joint chondrocytes against oxygen-induced free radical damage.…”
mentioning
confidence: 99%
“…In the meta-analysis conducted by Concoff et al, [34] the e cacy of multiple HA injections versus a single dose of HA was studied. The pooled data showed that a single HA injection was not signi cantly more effective than IA-Saline in a period of six months.…”
Section: Discussionmentioning
confidence: 99%
“…In a few studies the e cacy of single cross-linked HMW-HA has been investigated, though there exists a discrepancy between them. [33][34][35][36] Our utilized HMW-HA (Arthromac®, Novatex Bioengineering SA Switzerland) is one of these cross-linked products which is indicated for single intra-articular injection in knee OA patients. [37] The aim of current trial was to compare the e cacy and safety of the single cross-linked HMW injection versus triple injection of low-molecular-weight IA-HA among knee OA patients in terms of function and pain improvement during a six-month period.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a progressive disease that affects the activity of daily living in many people worldwide. Conservative treatments for OA include physiotherapy [1,2], dieting [3,4], hyaluronic acid intra-articular injection [5], and non-steroidal anti-in ammatory drugs (NSAIDs) [6], and they have certain bene cial effects. However, it is di cult to prevent OA progression, while analgesic drugs such as NSAIDs have adverse effects [7,8].…”
Section: Introductionmentioning
confidence: 99%